Identification and characterization of recombinant plasmids carrying the complete qa gene cluster from Neurospora crassa including the qa-1+ regulatory gene. - Schweizer, M (1981)
The early reactions in the catabolism of quinic acid in Neurospora crassa are controlled by at least four genes which are clustered on linkage group VII. Three of the loci (qa-2, qa-4, and qa-3) encode enzymes that convert quinic acid to protocatechuic acid. The fourth gene (qa-1) encodes a positive regulatory protein which, in the presence of quinic acid, leads to the de novo synthesis of the other proteins in the qa cluster. This communication describes a series of recombinant plasmids that span 36.5 kilobases of linkage group VII and contain the coding sequences for qa-2, qa-4, qa-3, and the qa-1 regulatory protein. The plasmids were obtained by partial digestion of wild-type N. crassa DNA with EcoRI and ligation into the cosmid cloning vehicle pHC79. Two independently derived plasmids (pMSK331 and pMSK335), each containing 36.5-kilobase inserts, were shown by transformation back into N. crassa to contain the entire qa gene cluster. A preliminary physical organization of the gene cluster is presented. An improved procedure for the transformation of N. crassa with plasmid DNA is also described.